Influence of Ni addition and heat treatment on phase transformation temperatures and microstructures of a ternary CuAlCr alloy - Dagdelen, F.; Aldalawi, M. A. K.; Kok, M.; Qader, I. N. (Springer Heidelberg, 2019)
In this paper, Cu85Al12Cr3 and Cu83Al12Cr3Ni2 (wt. %) high temperature shape memory alloys (HTSMA) were fabricated from highly pure powder elements by using an arc melter. After production, some pieces of alloys were subjected to heat treatment at 1073K for one hour. Then, Differential Scanning Calorimeter (DSC), Optical Microscopy (OM), X-Ray Diffraction (XRD), Vickers microhardness, and Scanning Electron Microscopy (SEM) analyses were carried out to investigate thermodynamic parameters, microstructure, crystal structure, mechanic properties, and to determine precipitation types in non-heat-treated and heat-treated alloys, respectively. According to the results of DSC measurements, both alloys showed a high temperature shape memory effect; also, the phase transformation temperatures of the alloys were affected by the heat treatment. The analysis of XRD patterns showed two different predominant microstructures in both alloys, i.e. and phases. Moreover, microstructural results showed the influence of Ni additive in decreasing the size of the grains and the number of the precipitates. In addition, micro-hardness, as a mechanic property, decreased through adding Ni to the CuAlCr alloy.
Keywords: Shape-Memory Alloys; Mechanical-Properties; Al; Behavior